Constitutional Status of Polish Intelligence Services since 1989 – Intelligence vs. the Police (Politeja, 2017)
The aim of the paper is to focus on two characteristic features which make it difficult to define precisely the constitutional position of Polish intelligence services. First of all, there is no concise concept referring to the place and role that Polish intelligence services should play after 1989. Secondly, intelligence services lack clear distinction from police services. Not only are these services organized in a similar way but also their tasks and powers are alike. Here the question arises: where is the border between intelligence services and police services which were created for different purposes and which have other methods of interfering in individual’s rights and freedom.